Gasdermin E: A Prospective Target for Therapy of Diseases - Liao, Xiu-Xiu; Dai, Yong-Zhao; Zhao, Yao-Zhong; Nie, Ke (Frontiers in Pharmacology, 2022)
Gasdermin E (GSDME) is a member of the gasdermin protein family, which mediates programmed cell death including apoptosis and pyroptosis. Recently, it was suggested that GSDME is activated by chemotherapeutic drugs to stimulate pyroptosis of cancer cells and trigger anti-tumor immunity, which is identified as a tumor suppressor. However, GSDME-mediated pyroptosis contributes to normal tissue damage, leading to pathological inflammations. Inhibiting GSDME-mediated pyroptosis might be a potential target in ameliorating inflammatory diseases. Therefore, targeting GSDME is a promising option for the treatment of diseases in the future. In this review, we introduce the roles of GSDME-driven programmed cell death in different diseases and the potential targeted therapies of GSDME, so as to provide a foundation for future research.